Diversity and stress tolerance in rhizobia from Parque Chaqueño region of Argentina nodulating Prosopis alba - Chávez Díaz, Lucía (2013)
The aim of this work was to investigate the genetic diversity, symbiotic effectiveness, drought tolerance, and indole acetic acid production of indigenous rhizobial populations in the Parque Chaqueño of Argentina able to nodulate Prosopis alba, the dominant forest tree of this region. The populations were sampled at five locations from the Arid, Semi-arid, and Humid Chaco in the Parque Chaqueño region. A set of rhizobial strains able to nodulate P. alba was obtained and selected based on their molecular diversity. Data obtained by BOX-PCR indicated that the highest molecular variability was observed in rhizobial isolates from Semi-arid Chaco. High level of indolic compound production and tolerance to osmotic treatment were significantly (p ≤ 0.05) correlated with water restrictions of the environments where the strains belonged. A small set of rhizobial strains that stimulate P. alba growth was selected from a large group of strains. The strains were identified by 16S rDNA sequencing as belonging to the genera Mesorhizobium, Bradyrhizobium, and Ensifer. To our knowledge, this is the first report of P. alba nodulation by strains other than Mesorhizobium chacoense, which was already described for the Parque Chaqueño.